2018
DOI: 10.1111/cfs.12604
|View full text |Cite
|
Sign up to set email alerts
|

Social workers' attitudes towards female victims of domestic violence: A study in one English local authority

Abstract: This paper aims to explore childcare social workers' attitudes towards female victims of domestic violence in England. The study discusses the concept of “mothering” and the processes through which mothers are potentially denigrated rather than empowered. Semi‐structured interviews were conducted with social workers in a single child protection agency to investigate their perceptions of domestic violence, its gendered nature, and the implications for their practice. Participants' responses were coded using the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…All studies acknowledged some good practice but showed that this was not reflective of most mothers' experiences. Social work aims to be a caring profession, but most mothers reported being blamed and made responsible for abuse perpetrated against them, being required to leave a violent partner, experiencing forced child removal and being treated callously by social workers (Neale 2018;Witt and Diaz 2018;Keeling and Van Wormer 2012;Lapierre 2008Lapierre , 2010Douglas and Walsh 2010;Ramsay 2017;and Johnson and Sullivan 2008). Humphreys and Absler's (2011) paper reviewed child welfare documents from the UK, the USA and Canada from 1900 to 2011, and the 'Failure to Protect' Working Group (2000) reviewed documentation across numerous jurisdictions.…”
Section: Mother Blame Social Work Child Welfare and Domestic Violementioning
confidence: 99%
See 4 more Smart Citations
“…All studies acknowledged some good practice but showed that this was not reflective of most mothers' experiences. Social work aims to be a caring profession, but most mothers reported being blamed and made responsible for abuse perpetrated against them, being required to leave a violent partner, experiencing forced child removal and being treated callously by social workers (Neale 2018;Witt and Diaz 2018;Keeling and Van Wormer 2012;Lapierre 2008Lapierre , 2010Douglas and Walsh 2010;Ramsay 2017;and Johnson and Sullivan 2008). Humphreys and Absler's (2011) paper reviewed child welfare documents from the UK, the USA and Canada from 1900 to 2011, and the 'Failure to Protect' Working Group (2000) reviewed documentation across numerous jurisdictions.…”
Section: Mother Blame Social Work Child Welfare and Domestic Violementioning
confidence: 99%
“…Mothers carried the emotional burden of abuse and continually felt blamed by professionals (Neale 2018). Witt and Diaz (2018) explored childcare social workers' attitudes towards female victims of domestic violence in England. Their study discussed the concept of mothering and the processes through which mothers were potentially denigrated rather than empowered.…”
Section: Mother Blame Social Work Child Welfare and Domestic Violementioning
confidence: 99%
See 3 more Smart Citations